Altruism Models In Islamic Consumption System - Muhammad Muflih (International Journal of Islamic Business and Economics (IJIBEC), 2017)
This study succeeded in proving that altruism is an inseparable element in the Islamic consumption system because it is able to lead a consumer to the best level of godliness. Just by assuming that , the formation of satisfaction in Islamic altruism cannot be determined by one stage. It is plotted into three stages, namely: (1) compassion utility originating from the spirit of social emotion, enabling it to create as an emblem of emotional satisfaction; (2) rationalizing social−spiritual gain originating from a motivation to reach a religiously promised reward for a sacrifice made by a consumer for the poor and needy, resulting in as an indicator of a consumer’s gains; and (3) God and human relationship originating from the spirit of a consumer to always be close to God absent of reward, symbolized by . What is unique is the three forms of altruism have a one direction altruism pattern unknown to among economists and altruists. This finding especially contributes to the Islamic Philanthropic Institution in identifying a class of altruism in Muslims. Evidently, their altruism pattern is closely attached to their consumption system.